A multi-omics approach combining causal inference and in vivo validation identifies key protein drivers of alcohol-associated liver disease - Zhou, Qingyi; Ma, Xuan; Cui, Qianqian; Zhang, Lei; Yao, Chao; Zhang, Zilu; Wang, Xiaoli; Chu, Liang (Frontiers in Immunology, 2025)
BackgroundAlcohol-associated liver disease (ALD) constitutes a global health crisis, yet the molecular mechanisms driving its pathogenesis remain unresolved, critically impeding the development of effective therapeutics. A fundamental challenge is the differentiation of correlational biomarkers from the causal drivers of disease. Here, we perform a systematic characterization of the ALD causal proteome to uncover novel pathogenic mediators and prioritize therapeutic targets.MethodsWe implemented a multi-stage pipeline integrating human genetics with multi-level experimental validation. A two-sample Mendelian randomization (MR) framework, leveraging large-scale plasma proteomics and ALD GWAS data, was employed to nominate proteins causally linked to ALD. These candidates underwent functional enrichment analysis to delineate their biological roles. To rigorously control for confounding by genetic linkage, findings were validated using SMR. We then employed single-cell RNA sequencing from a murine ALD model to determine the hepatic cellular origins of the validated targets. Finally, their functional relevance was established in vivo using a chronic-plus-binge ethanol feeding mouse model.ResultsOur MR analysis identified 17 proteins with a putative causal association with ALD. Functional enrichment analysis implicated these candidates in inflammatory and immune response pathways. After stringent SMR validation, we identified four high-confidence causal proteins: TREML2 (Triggering Receptor Expressed on Myeloid cells-like 2) and MMP12 (Matrix Metallopeptidase 12) as risk factors, and PLA2R1 (Phospholipase A2 Receptor 1) and MAX (MYC Associated Factor X) as protective factors. Single-cell transcriptomics resolved the cellular sources of these proteins within the liver, identifying hepatic myeloid cells (macrophages and monocytes) as the primary source of the risk-promoting TREML2 and MMP12. In contrast, the protective protein PLA2R1 was predominantly expressed in hepatocytes, while MAX exhibited broad expression. These genetic predictions were phenocopied in our ALD mouse model; hepatic expression of Treml2 and Mmp12 was significantly upregulated, whereas Pla2r1 and Max were downregulated, corroborating their respective roles in disease pathogenesis.ConclusionBy systematically integrating genetic causal inference with multi-level functional genomics, we identify and validate four causal protein drivers of ALD. Our findings unveil a novel pathogenic axis where ALD risk is governed by a balance between pro-inflammatory, matrix-remodeling myeloid cells (driven by TREML2/MMP12) and homeostatic hepatocyte functions (mediated by PLA2R1/MAX). These genetically validated targets provide critical insights into ALD pathophysiology and represent promising, mechanistically-defined avenues for therapeutic intervention.